Development of algorithm to characterize flavonoids classes - Che Noh, Che Hafizah; Mohamed Azmin, Nor Fadhillah; Amid, Azura; Asnawi, Ani Liza; Ibrahim, Siti Noorjannah (Institute of Electrical and Electronics Engineers Inc., 2017)
Flavonoids is one of the bioactive compounds that are currently used in pharmaceutical and medicinal industries due to their health benefit. The focus of current research is mainly on the extraction and isolation of bioactive compounds; non to date has explored on the identification of flavonoids classes under the Fourier Transform Infrared spectroscopy (FTIR). This gap presents an opportunity to develop an algorithm which can identify the distinct wavenumber range of flavone, flavanone and flavonol for their characterization in the FTIR spectrum. Development of algorithm based on PCA for the analysis and identification of flavonoids classes based on FTIR spectrum is introduced. Based on the results, five wavenumbers range has been identified as the distinct characteristics of flavonol, flavone and flavanone hence used for their identification.